2018
DOI: 10.1016/j.matdes.2018.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Ionic liquids for the control of the morphology in poly(vinylidene fluoride-co-hexafluoropropylene) membranes

Abstract: Abstract:The development of polymer membranes with tailored micro-morphology and wettability is a demand in the areas of filtration, sensors, and tissue engineering, among others. The thermoplastic copolymer poly(vinylidene fluoride-cohexafluoropropylene) (PVDF-HFP), is one of the most widely used polymers for these applications due to its good mechanical and thermal properties, biocompatibility and low density. Although the control of the PVDF-HFP morphology is a complicated task, the introduction of ionic li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 46 publications
1
13
0
Order By: Relevance
“…The Psf/[DMIM]­[Cl] and Psf/[EMIM]­[PF 6 ] membranes presented an initial weight loss of 2%, which was because of the loss of moisture as likely observed in the neat Psf membrane. Interestingly, the Psf/[DMIM]­[Cl] membrane showed a mass loss of about 10% at about 250 °C, which was because of the degradation of ILs containing [Cl] ions, which generally have less thermal stability. , …”
Section: Resultsmentioning
confidence: 99%
“…The Psf/[DMIM]­[Cl] and Psf/[EMIM]­[PF 6 ] membranes presented an initial weight loss of 2%, which was because of the loss of moisture as likely observed in the neat Psf membrane. Interestingly, the Psf/[DMIM]­[Cl] membrane showed a mass loss of about 10% at about 250 °C, which was because of the degradation of ILs containing [Cl] ions, which generally have less thermal stability. , …”
Section: Resultsmentioning
confidence: 99%
“…The addition of the ILs manipulates the morphology of the membranes, where ILs are known to be structure-directing agents. For instance, GSaiz et al [37] studied the effect of ILs on the morphology of a PVDF-HFP membrane. The Scanning Electron Microscopy (SEM) results showed the presence of several morphologies and different hydrophobic properties depending on the selected IL.…”
Section: Preparation Of Polymerized Ionic Liquid Membranesmentioning
confidence: 99%
“…[dema][TfO] itself exhibits high proton conductivity due to the presence of hydrogen-bond networks and remains stable over a wide range of temperature [21]. It was also reported that electrolytes containing both phosphoric acid and PIL supported better interfacial electrochemical activities (oxygen reduction reaction; ORR and hydrogen evolution reaction; HER) in comparison to the electrolytes based only on phosphoric acid [22,23].…”
Section: Introductionmentioning
confidence: 99%